TAXATION AND FORMS OF ORGANISING BUSINESS ACTIVITIES - Đinđić, Srđan (Economic Annals, 2013)
This paper takes sample tax regimes and tendencies from the developed countries in the EU-15 and the USA, and uses them to analyse the influence of taxation on the choice of organisational form of profit-oriented entities in Serbia. In order to understand how the procedure of taxation affects the sphere of business decision-making it is necessary to focus on the tax status of business losses and valorisation and the effects of the double taxation of dividends. The rule of successive deduction of losses ensures the fiscally transparent entity receives a tax saving in the form of a reduction of the present value of the total paid tax. Meanwhile the corporation is handicapped because it postpones loss deductions, that is, it postpones tax saving, which directly influences the level of the present value of saved tax. The global trend of gradually moving from the classical system towards shareholder relief provision, above all in the form of a reduced withholding tax rate on dividends, has two opposing features: it simplifies the tax procedure while neglecting the distributional aims (consequences) of taxation. The analysis of a particular practical example from the Serbian tax context enables us to draw a conclusion in relation to the relative taxes paid by entrepreneurs versus enterprises. The developed countries favour fiscally transparent entities, whereas Serbia allocates tax privileges to enterprises.